MATHEMATICAL MODEL OF THE SPREAD OF CANINE DISTEMPER VIRUS (CDV) - Ayuning Tias, Desya
Canine Distemper Virus (CDV) is currently a threat to carnivorous animals worldwide, especially to some endangered animals such as the Sumatran tiger. This disease spreads easily and can lead to serious infections and even death. There is no specific treatment to kill canine distemper virus yet. However, prevention of this viral disease can be done by giving a series of vaccinations from a young age. In this thesis, a mathematical model of the spread of canine distemper virus (CDV) is presented. This model is influenced by the presence of a vaccine with the aim of reducing the spread of CDV. From this model, two equilibrium points are obtained, namely the disease-free equilibrium point and the endemic equilibrium point. In addition, the value of the basic reproduction number is also obtained. The numerical simulation results show that the greater the contact rate between the susceptible and the infected, the smaller the increase in the number of vaccinated populations and the greater the increase in the number of infected populations. Therefore, increasing vaccination can reduce the spread of CDV.